Analysis of the Development and Implementation of Regulations Related to the Implementation of Electronic-Based Government Systems in Indonesia to Improve Public Services - Ulum, Bahrul; Soesatyo, Bambang (Asian Journal of Social and Humanities, 2025)
The implementation of the Electronic-Based Government System (EGO) in Indonesia is a critical step to improve the efficiency and quality of public services. The regulations underlying the implementation of EGO, such as Presidential Regulation No. 95 of 2018 concerning the Electronic-Based Government System, aim to encourage digital transformation in government bureaucracy. However, even though these regulations already exist, challenges in their implementation still arise, both in terms of infrastructure, human resources, and system integration between government agencies. This study aims to analyze the development of regulations that support the implementation of EGO and evaluate their implementation in the context of improving the quality of public services in Indonesia. By understanding the challenges and potential of EGO, it is expected that more effective policies can be created to accelerate digital transformation and increase government transparency and accountability in serving the public.